You are on page 1of 7

Exponential Dichotomy

Zhisheng Shuai Department of Mathematical and Statistical Sciences University of Alberta
April 11, 2005

This lecture note is only used for my presentation on the course Math 525 “Ordinary Differential Equations IIB” taught by Prof. Michael Li. Most materials are chosen from W.A. Coppel’s book. Consider linear autonomous system x (t) = Ax(t), and nonhomogeneous system x (t) = Ax(t) + f (t),
n 1

(L) (N L)

where A is a constant n × n matrix, x ∈ R , t ∈ R and f ∈ C . Then we have equivalence of following three statements: (a) Reσ (A) = 0; (b) (L) has no nontrivial bounded solution for t ∈ R; (c) For each f bounded for t ∈ R, (N L) has a unique solution x(t) that is bounded for all t ∈ R, where
∞ t

x(t) =
−∞

K (t − s)f (s)ds =
−∞

eA(t−s) P f (s)ds −
t

eA(t−s) Qf (s)ds.

(∗)

Here, K ( t − s) = eA(t−s) P, t≥s −eA(t−s) Q, t < s,

and Reσ (AP ) < 0, Reσ (AQ) > 0, P + Q = I , P 2 = P . Clearly, (a) ⇔ (b). Now want to show (b) ⇔ (c). First, if (b) holds, then (a) holds. Furthermore, we can get a solution of the form (∗). Now verify x(t) is a bounded solution of (N L). In fact,
t

x (t) = P f (t) +
−∞

AeA(t−s) P f (s)ds + Qf (t) −
t t ∞ t

AeA(t−s) Qf (s)ds = f (t) + Ax(t),

and |x(t)| ≤

Ke−α(t−s) ds +

Ke−α(s−t) ds

||f || ≤

−∞

2K ||f ||, α

where ||f || = supt∈R |f (t)| since from Reσ (AP ) < 0 and Reσ (AQ) > 0, we have respectively |eA(t−s) P | ≤ Ke−α(t−s) , t ≥ s, |eA(t−s) Q| ≤ Ke−α(s−t) , s ≥ t, where α > 0 and K > 0. From the uniqueness in (b), by superposition principle, we can get the uniqueness in (c). Conversely, if (c) holds, by superposition principle, we can get the conclusion (b). 1

using exponential dichotomy. t ≥ s. (3) =⇒ (5). |X (t)P X −1 (t)| ≤ Ke0 = K. The third condition says that the ‘angle’ between these two subspaces remains bounded away from zero since when the angle θ → 0 the norms of two project tend to infinity. M0 are positive constants and ξ is an arbitrary constant vector. (a) doesn’t work. The autonomous equation x (t) = A0 x(t) (4) has an exponential dichotomy on J0 = (0. The equivalent definition of exponential dichotomy is to change conditions (2) and (3) to the following three conditions |X (t)P ξ | ≤ K0 e−α(t−s) |X (s)P ξ | for t ≥ s. L0 .. (1) where the n × n coefficient matrix A(t) is continuous on an interval J . (6) and (7). we study the existence of bounded solution under small perturbation of corresponding linear nonautonomous system. and (I − P )(I − P ) = I − P . s ≥ t.e. (2). Since P is a projection. (2) and |X (t)(I − P )X −1 (s)| ≤ Le−β (s−t) for s ≥ t.Note that for nonautonomous system. we have |X (t)P ξ | = |X (t)P X −1 (s)X (s)P ξ | ≤ |X (t)P X −1 (s)| |X (s)P ξ | ≤ Ke−α(t−s) |X (s)P ξ |. |X (t)(I − P )ξ | = |X (t)(I − P )X −1 (s)X (s)(I − P )ξ | ≤ |X (t)(I − P )X −1 (s)| |X (s)(I − P )ξ | ≤ Le−β (s−t) |X (s)(I − P )ξ |. Suppose the projection P has rank k . The equation (1) is said to posses an exponential dichotomy if there exists a projection P and positive constants K. Then the first condition (5) says that there is a k -dimensional subspace of solutions tending to zero uniformly and exponentially as t → ∞. It has an ordinary dichotomy on above J0 if and only if all eigenvalues of A0 with zero real part are of simple type. and |X (t)P X −1 (t)| ≤ M0 for all t. (3) It is said to posses an ordinary dichotomy if the inequalities (2) and (3) hold with α and β not positive but zero. and an ordinary dichotomy with P = I if and only if it is uniformly stable. |X (t)(I − P )ξ | ≤ L0 e−β (s−t) |X (s)(I − P )ξ | for s ≥ t. The proof for equivalence of definition of exponential dichotomy is following: First. we can generalize it to get the concept of exponential dichotomy. ∞) if and only if no eigenvalues of the constant matrix A0 has zero real part. L. α. P 2 = P . (5) (6) (7) where K0 . Then. The equation (1) has an exponential dichotomy with P = I if and only if it is uniformly asymptotically stable. Let X (t) be a fundamental matrix for the linear differential equation x (t) = A(t)x(t). and 2 . β such that |X (t)P X −1 (s)| ≤ Ke−α(t−s) for t ≥ s. The second condition (6) says that there is a (n − k )-dimensional subspace of solutions tending to zero uniformly and exponentially as t → −∞. However. i.

the Banach space of all Lebesgue integrable vector functions f as L.. (12) Similarly. Proof of Theorem 1. 0 |f (s)|ds is bounded. t |f (s)|ds is bounded. supt≥0 |f (t)| < ∞. we get |X (t)P X −1 (s)η | ≤ ≤ ≤ |X (t)(I − P )X −1 (s)η | ≤ ≤ ≤ K0 e−α(t−s) |X (s)P X −1 (s)η | K0 e−α(t−s) |X (s)P X −1 (s)| |η | K0 M0 e−α(t−s) |η |. for any η .e. we can show that x(t) is a solution of (8) and x(t) is bounded for every f ∈ C if (1) has exponential dichotomy. Then we have conclusions as follow: Theorem 1 (W. The inhomogeneous equation (8) has at least one bounded solution for every function f ∈ L if and only if the homogeneous equation (1) has an ordinary dichotomy.. Consider the inhomogeneous equation x (t) = A(t)x(t) + f (t). or bounded. L ⊂ M and C ⊂ M . and the Banach space of all bounded vector functions f as C . Correspondingly. 0 (9) (10) (11) ||f ||L = and ||f ||C = sup |f (t)|.e. setting ξ = X −1 (s)η . thus (2) and (3) hold. Now assume the fundamental matrix X (0) = I for (1) and the interval J = J0 = (0. there exist real constant C. Suppose (1) has bounded growth. The inhomogeneous equation (8) has at least one bounded solution for every function f ∈ M if and only if the homogeneous equation (1) has an exponential dichotomy.e. then for every f ∈ M . i.e. L0 e−β (s−t) |X (s)(I − P )X −1 (s)η | L0 e−β (s−t) |X (s)(I − P )X −1 (s)| |η | L0 (M0 + 1)e−β (s−t) |η |. ∞). x(t) is still a bounded solution of (8) since t 0 e−α(t−s) |f (s)|ds ≤ (1 − e−α )−1 t t+1 |f (s)|ds 3 ..A. Coppel).A. or Lebesgue ∞ integrable on J0 . (8) where vector function f (t) is locally integrable on J0 . Clearly. then consider the solution t x(t) = 0 X (t)P X −1 (s)f (s)ds − t ∞ X (t)(I − P )X −1 (s)f (s)ds. denote the Banach space of all locally integrable vector functions f as M . Theorem 2 (W. 2 and 3 Step 1: Sufficiency If (1) has exponential dichotomy or ordinary dichotomy.A. i. i. Furthermore.Conversely. Then the inhomogeneous equation (8) has at least one bounded solution for every function f ∈ C if and only if the homogeneous equation (1) has an exponential dichotomy. Coppel). with norm t+1 t+1 ||f ||M = sup t≥0 t ∞ |f (s)|ds. t ≥ s. t≥ 0 respectively. µ such that its fundamental matrix X (t) satisfies |X (t)X −1 (s)| ≤ Ceµ(t−s) . if (1) has exponential dichotomy. for t ≥ s. i. Theorem 3 (W.. Coppel). s ≥ t. |f (s)|ds.

Then there exists a least constant rB = rB (P ) > 0 such that. If f is a function in B which vanishes for t > t1 . where B denote any one of the Banach spaces L. Step 2: Projection and a lemma Let V1 be the subspace of Rn consisting of the initial values of all bounded solutions of (1). since it is bounded. Therefore. Then G is continuous except on the line s = t. the unique bounded solution y (t) of (8) with y (0) ∈ V2 satisfies ||y ||C ≤ rB ||f ||B .e. < ∞. Step 4: Proof of Theorem 1 4 . If (1) has ordinary dichotomy. Lemma 1. We will show that T has a closed graph. x(t) is still a bounded solution of (8). by lemma 1. the equation (8) does have a unique bounded solution y (t) with y (0) ∈ V2 . Suppose fn → f in B and yn = T fn → y in C . It now follows from the Closed Graph Theorem that the linear map T is continuous.. it is bounded from (5) since t1 y (t) = X (t)P 0 X −1 (u)f (u)du for t ≥ t1 . i. M. for every f ∈ B . Suppose the equation (8) has a bounded solution for every function f ∈ B . the map T : f → y is linear. and the existence of a least one can be deduced immediately. t1 and y (0) = −(I − P ) 0 X −1 (u)f (u)du ∈ V2 since X (t)y (0) exponentially increases from (6). then for every f ∈ L. Then. where it has a jump discontinuity. y = T f .and t ∞ e−α(s−t) |f (s)|ds ≤ (1 − e−α )−1 t+1 |f (s)|ds. Moreover. for every f ∈ B . Thus y (t) is a solution of the equation (8). Proof. Moreover. It follows from the superposition principle that. This proves the existence of some constant rB > 0. we have ||y ||C ≤ rB ||f ||B . Thus. s) = −X (t)(I − P )X −1 (s) for 0 ≤ t < s. Hence t t t t ∞ |f (t)|dt 0 y (t) − y (0) = lim n→∞ 0 yn (s)ds = lim n→∞ (A(s)yn (s) + fn (s))ds = 0 0 (A(s)y (s) + f (s))ds. then t1 t y (t) = 0 G(t. u)f (u)du = 0 X (t)P X −1 (u)f (u)du − t t1 X (t)(I − P )X −1 (u)f (u)du is a solution of (8). Set P denote the projection from Rn to V1 with nullspace V2 . C . Step 3: Construction of the bounded solution Put X (t)X −1 (s) for 0 ≤ s < t G(t. t t y (0) = limn→∞ yn (0) ∈ V2 and for any fixed t we have 0 f (s)ds = limn→∞ 0 fn (s)ds. and let V2 be the fixed subspace of Rn supplementary to V1 .

Namely. |x1 (t)| ≤ N |x(s)| for s ≤ t ≤ s + r. |G(t. If. u)ξdu ≤ rL ||f ||L = rL h|ξ |. 5 (14) . then Proof. s+ h |y (t)| = s G(t. Let x(t) be a solution of the corresponding homogeneous equation (1) and put x1 (t) = X (t)P X −1 (t)x(t). (s−t) for 0 ≤ t < s. it still holds. Dividing by h and letting h → 0. |x2 (t)| ≤ N |x(s)| for max(0. Then ||f ||C = 1 and hence. respectively. s − r) ≤ t ≤ s.Let ξ be any constant vector and let f be the function defined by f (t) = ξ 0 for s ≤ t ≤ s + h otherwise. Suppose the equation (8) has a bounded solution for every f ∈ C with rC in lemma 1. we obtain for any t = s |G(t. s)ξ | ≤ rL |ξ |. for some fixed s ≥ 0. and φ(t) = 0 for t ≥ t1 . since ξ is arbitrary. for some fixed s ≥ 0. then If. Take f (t) = |x2 (t)| ≤ eN |x(s)|e−rC −1 |x1 (t)| ≤ eN |x(s)|e−rC −1 (t−s) for s ≤ t < ∞. t0 = t. |X (t)(I − P )X −1 (s)| ≤ rL 0 ≤ t < s. (13) Putting t1 = t. when t = s. By continuity. and |X (t)P X −1 (s)| ≤ rL . u)x(u)|x(u)|−1 du ≤ rC ||f ||C = rC for 0 ≤ t0 ≤ t1 and t ≥ 0. Therefore. s)| ≤ rL . Then f ∈ L and ||f ||L = h|ξ |. φ(t)x(t) . Step 5: Lemma from boundedness to exponential decay Lemma 2. we have t1 t0 G(t. Hence. |x(t)| where x(t) = X (t)ξ is any nontrivial solution of the homogeneous equation (1) and φ(t) is any continuous real-valued function such that 0 ≤ φ(t) ≤ 1 for all t ≥ 0. we obtain t |X (t)P ξ | t0 |X (u)ξ |−1 du ≤ rC for t ≥ t0 ≥ 0. x2 (t) = X (t)(I − P )X −1 (t)x(t). by the arbitrary nature of φ. Thus (1) has ordinary dichotomy. 0 ≤ s < t. where s ≥ 0 and h > 0.

and obtain the exponential dichotomy with K = erL and −1 α = rC . t ≥ s. replacing s by s − rC and t1 by s in the second inequality (17). Thus In the same way and hence |X (t)(I − P )X −1 (s)| ≤ µrC C for t ≤ s. 6 . it follows by multiplying e−rC and integration that s t0 t1 s |X (u)P ξ |−1 du ≤ e−rC −1 (t−s) t t0 |X (u)P ξ |−1 du for t ≥ s ≥ t0 . −1 (15) (t−s) since x(t) = X (t)ξ . equation (1) has ordinary dichotomy with K = rL and α = 0.t1 |X (t)(I − P )ξ | t |X (u)ξ |−1 du ≤ rC for t ≤ t1 ≤ ∞. from the inequality (14) we obtain |X (t)P X −1 (s)| ≤ µrC C [1 − e−µ(t−s) ]−1 for t > s. |X (u)(I − P )ξ |−1 du for t ≤ s ≤ t1 . Replacing ξ by P ξ . for every solution x(t) of (1) and every s ≥ 0. Using the inequality (14). |X (t)P X −1 (s)| ≤ (1 + µrC )Ceµ(t−s) for t ≥ s. Replacing t0 by s and s by s + rC in the inequality (16) we obtain for t ≥ s + rC rC |x(s)|−1 ≤ N s+rC s |x1 (u)|−1 du ≤ ee−rC −1 (t−s) s t |x1 (u)|−1 du. this proves the first assertion of the lemma. The proof of the second assertion is similar. this gives for t ≤ s |X (t)(I − P )X −1 (s)ξ | ≤ rC s ∞ −1 |X (u)X −1 (s)ξ |−1 du ≤ rC C −1 |ξ |−1 s ∞ −1 eµ(s−u) du . the equation (8) has a bounded solution for every f ∈ C and for every f ∈ L. Hence in Lemma 2 we can take N = rL . (I − P )ξ . this gives for t ≥ s + rC t −1 |x1 (t)| ≤ rC s |x1 (u)|−1 du ≤ eN |x(s)|e−rC −1 (t−s) . This is all the information that we will actually use. (18) Similarly. |X (t)(I − P )X −1 (s)| ≤ µrC Ceµ(t−s) for t ≥ s. (16) |X (u)(I − P )ξ |−1 du ≤ e−rC −1 (s−t) t t1 (17) We can write x(t) = X (t)ξ for some vector ξ . Replacing ξ by X −1 (s)ξ and putting t1 = ∞ in the inequality (15). Step 7: Proof of Theorem 3 Without loss of generality. By Theorem 1 and its proof. Since the same inequality evidently holds also for s ≤ t ≤ s + r. Step 6: Proof of Theorem 2 Since C ⊂ M and L ⊂ M . respectively. assume C ≥ 1 and µ > 0 in the following inequality |X (t)X −1 (s)| ≤ Ceµ(t−s) .

for 0 ≤ t ≤ s. −1 (s−t) References [1] W. (19) (t−s) for 0 ≤ s ≤ t. 7 . 1978.A. Springer. Dichotomies in Stability Theory. −1 1 + 2µrC 1 + µrC . It now follows from Lemma 2 using (18) and (19) that |X (t)P X −1 (s)| ≤ e(1 + 2µrC )Ce−rC |X (t)(I − P )X −1 (s)| ≤ eµrC Ce−rC Thus (1) has an exponential dichotomy.By using this inequality for t − s ≥ h. Vol 629. Lecture Notes in Mathematics. we get |X (t)P X −1 (s)| ≤ (1 + 2µrC )C for all t ≥ s. Berlin. where h = µ−1 log and the previous inequality for t − s ≤ h. Coppel.